2015
DOI: 10.1371/journal.pone.0131350
|View full text |Cite
|
Sign up to set email alerts
|

miR-203 Inhibits Frizzled-2 Expression via CD82/KAI1 Expression in Human Lung Carcinoma Cells

Abstract: CD82/KAI1, a member of the tetraspanin superfamily, is a suppressor of metastasis and CD82 inhibits canonical Wnt signaling via downregulation of several Frizzled (FZD) isoforms, resulting in accumulation of β-catenin at the cell membrane. In this study, we investigated the mechanism through which CD82 inhibited FZD expression by examining the effects of microRNAs (miRNAs). The miRanda algorithm predicted 11 miRNAs from FZD sequences. Among these miRNAs, CD82 caused upregulation of miR-203 (by 2.095-fold) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(43 reference statements)
0
20
0
Order By: Relevance
“…CD82 downregulates the level of the transmembrane protein Frizzled, probably by enhancing miR-203 expression, and thereby reduces Wnt signaling [61,62]. CD82 also inhibits the expression of glycogen synthase kinase-3β (GSK-3β) and casein kinase 1α (CK1α), resulting in less phosphorylation and extranuclear accumulation of β-catenin [62].…”
Section: In Solid Tumor Cells Cd82 Regulates the Signaling Of Membramentioning
confidence: 99%
“…CD82 downregulates the level of the transmembrane protein Frizzled, probably by enhancing miR-203 expression, and thereby reduces Wnt signaling [61,62]. CD82 also inhibits the expression of glycogen synthase kinase-3β (GSK-3β) and casein kinase 1α (CK1α), resulting in less phosphorylation and extranuclear accumulation of β-catenin [62].…”
Section: In Solid Tumor Cells Cd82 Regulates the Signaling Of Membramentioning
confidence: 99%
“…The inhibition of KAI1 was related to EGFR over-expression, as well as EGFR mutations in non-small cell lung cancers (15). KAI1 suppress metastasis by inhibition of Wnt signaling pathway through up-regulation of miR-203 and directly down-regulation of FZD2 in lung cancer (16). Thus, it was accepted that KAI1 suppresses tumor metastasis via multiple signaling pathway and considered as a valuable marker for assessing metastasis potential (17).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Xu et al also found that this gene is a target of miR-34c in an osteosarcoma model [131]. Moreover, recent evidence suggests the targeting of the Wnt/β-catenin-related receptor, Frizzled-2, by miR-203, even if no direct binding was attested [139]. In addition, it was found that miR-203 indirectly increases the expression of the Dickkopf Wnt signaling pathway inhibitor 1 (DKK-1), a secreted Wnt-related pathway inhibitor reported to impede osteogenesis in MSCs [140].…”
Section: The Wnt Pathwaymentioning
confidence: 99%